Applications of Microcomputers in Patient Care - Eden, Henry S. (1979)
This paper serves as an introduction to two sessions on microcomputer applications in patient care. It describes several advantages offered by microcomputers in the design of medical devices--flexibility, reliability, smallness, and low power consumption. It concludes by discussing eight categories of microcomputer application.